2017
DOI: 10.20884/1.jks.2017.12.1.677
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Karakteristik Remaja Dengan Perilaku Bullying Pada Siswa SMP Di Kota Padang

Abstract: Bullying is a phenomenon that is common and universal problems in school- ABSTRAKBullying merupakan fenomena yang umum dan masalah yang universal pada anak usia sekolah. Bullying dapat menimbulkan efek yang serius/ negatif terhadap kesehatan mental dan kesejahteraan anak. Penelitian ini bertujuan untuk mengidentifikasi prevalensi perilaku bullying pada siswa SMP di Kota Padang. Desain penelitian adalah deskriptif analitik dengan pendekatan cross sectional study. Sampel adalah siswa SMP Negeri 31 Padang, SMP 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
2
1
0
4
Order By: Relevance
“…Bullying in schools carried out by students does not only occur at the national level, but also occurs at the level of the province of West Sumatra. This is in accordance with data from the Padang Police during 2014 to 2015 the number of reports of bullying cases in schools is quite high both at the elementary, junior high, high school levels, namely as many as 72 cases of bullying reported in the form of acts of persecution, bullying, harassment and unpleasant acts (Hermalinda et al, 2017). Furthermore, based on data from the Padang Police in January-July 2016, 16 cases of bullying were reported and in January-May 2017 as many as 44 cases of bullying.…”
Section: Introductionsupporting
confidence: 90%
“…Bullying in schools carried out by students does not only occur at the national level, but also occurs at the level of the province of West Sumatra. This is in accordance with data from the Padang Police during 2014 to 2015 the number of reports of bullying cases in schools is quite high both at the elementary, junior high, high school levels, namely as many as 72 cases of bullying reported in the form of acts of persecution, bullying, harassment and unpleasant acts (Hermalinda et al, 2017). Furthermore, based on data from the Padang Police in January-July 2016, 16 cases of bullying were reported and in January-May 2017 as many as 44 cases of bullying.…”
Section: Introductionsupporting
confidence: 90%
“…This is related to the level of depression in the family which is channeled into bullying behavior between children or adolescents. This result is also supported by the research of (Herman et al, 2018) who found that most adolescents with moderate to low economic levels tend to be directly involved in bullying. According to some experts, the tendency of students to be bullies is due to family factors.…”
Section: Discussionsupporting
confidence: 71%
“…Research conducted in Padang city in 2016 in junior high schools showed that 89.4% of students had bullied schoolmates either physically or verbally in the last six months. Further analysis showed a weak relationship between the school environment, the support of groups and teachers and bullying behaviours but there was no significant relationship between school pressure and bullying behaviour (Herman, Nurshal, & Oktarina, 2017).…”
Section: Introductionmentioning
confidence: 79%